Bakery inventory management system for Norijah Bakery / Nurfatin Najwa Mustapha - Mustapha, Nurfatin Najwa (2017)
The research is discovering the problems with manual inventory management and the solution proposed to solve the problems for the stakeholder, Norijah’s Bakery. The research is focusing on the inventories used in the organization, which consist of the items and ingredients used by the bakery in their daily business process. The purpose of conducting this research was to solve the problems and issues of inventory management of the stakeholder. There were so many problems arises and failure in manual inventory management such as unorganized business flow, inventories spoilage and loss of data. The system was created to help the owner smoothen the business process besides ensuring the security of the company’s assets. Besides, the system is developed using the Waterfall Model of the Software Development Life Cycle by implementing the three important stages which is requirements gathering, system design and implementation. This system also built as a standalone software using Java as the programming language. It is built as standalone software because it will be used only in the stakeholder store. The system also gives user a great experience in viewing the system interfaces and use the system. After the research is done, the deliverables at each stage is achieved. Some of the findings are such as the System Requirement Specification(SRS), Software Design Document(SDD), and the system design. Even though this research has been completed, there still a lot of enhancement can be done. This research can be improved by widen the scopes of the research by including the sales, products and machinery of the inventory management as inventory management field is big. With the scopes widen, the functionalities of the system can be increased. As a conclusion, this research is proved to be beneficial to the stakeholders.